2019
DOI: 10.18632/oncotarget.26958
|View full text |Cite
|
Sign up to set email alerts
|

ETHE1 overexpression promotes SIRT1 and PGC1α mediated aerobic glycolysis, oxidative phosphorylation, mitochondrial biogenesis and colorectal cancer

Abstract: Ethylmalonic Encephalopathy Protein 1 ( ETHE1 ) is a sulfur dioxygenase that regulates cellular H 2 S levels. We previously demonstrated a significant increase of ETHE1 expression in "single-hit" colon epithelial cells from crypts of patients with Familial Adenomatous Polyposis (FAP). Here, we report elevated levels of ETHE1 expression and increased mitochondrial density occurring in-situ in phenotypically normal FAP co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…For example, Witherspoon et al 14 indicated that the constitutive expression of ETHE1 increases aerobic glycolysis ("Warburg effect"), oxidative phosphorylation, and mitochondrial biogenesis in colorectal cancer (CRC) cell lines. 35 Yang and colleagues 36 suggested that mitochondrial biogenesis and maintenance may play an important part in tumor cell survival during CRC progression. In our study, our data showed that upregulated MCU promotes mitochondrial biogenesis in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Witherspoon et al 14 indicated that the constitutive expression of ETHE1 increases aerobic glycolysis ("Warburg effect"), oxidative phosphorylation, and mitochondrial biogenesis in colorectal cancer (CRC) cell lines. 35 Yang and colleagues 36 suggested that mitochondrial biogenesis and maintenance may play an important part in tumor cell survival during CRC progression. In our study, our data showed that upregulated MCU promotes mitochondrial biogenesis in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…MCU-induced mitochondrial Ca 2+ uptake promotes mitochondrial biogenesis in CRC cells Several recent studies have reported the biological role of increased mitochondrial biogenesis in CRC tumorigenesis. 14,15 Therefore, we further explored the correlation between the expression of MCU and mitochondrial biogenesis in CRC cells. As shown in Fig.…”
Section: Upregulation Of Mcu Enhances the Mitochondrial Ca 2+ Uptake mentioning
confidence: 99%
“…The ER-mitochondrial contacts do not occur randomly, but on specific domains termed MAMs, which have a well-defined structure with several proteins present at both the OMM and the ER membrane [118]. MAMs allow a better transport of Ca 2+ to mitochondria and regulate spikes of activity through Ca 2+ transport from the ER to the mitochondria [119].The alteration of MAMs yields to the lack of Ca 2+ homeostasis and mitochondrial biogenesis impairment [97,116,120,121].…”
Section: The Role Of the Mamsmentioning
confidence: 99%
“…Interestingly, higher ETHE1 expression lowered cellular H2S concentrations (measured by lower glutathione persulfide levels), resulting in increased phosphodiesterase activity (PDE), and adenosine monophosphate-activated protein kinase (AMPKp), sirtuin1 (SIRT1), and peroxisome proliferation-activated receptor γ-coactivator-1α activation (PGC1α, 18). In a murine xenograft model, high ETHE1 expression also accelerated colon cancer cell line growth, with increased Ki-67 and CD31 expression, reflecting increased cell growth with concomitant intensified tumor angiogenesis (18). Conversely, a comparison of twenty colonic adenocarcinomas to patient-matched benign tissues revealed lower ETHE1 mRNA and protein expression in malignant tissues compared to benign (19).…”
Section: Discussionmentioning
confidence: 89%